Variability of selected hematological and biochemical markers in marathon runners - Kamińska, Joanna; Podgórski, Tomasz; Pawlak, Maciej (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The marathon is an increasingly popular form of athletic competition, especially among amateur runners. It seems, therefore, important to determine how this type of exercise affects the runner’s body. Aim of Study. The aim of the study was to identify hematological and biochemical changes in the blood of amateur runners after a marathon run. Material and Methods. The study involved 10 male runners aged from 28 to 42 years. Their blood was collected from the fingertip four times: a day before the competition and one, three and five days after the race, and subjected to hematological and biochemical analysis. Results. The results revealed a statistically significant increase in the number of leukocytes, including monocytes and granulocytes, creatine kinase (CK) and lactate dehydrogenase (LDH) activity, urea concentration, and ferric reducing ability of plasma (FRAP). On the other hand, the values of certain indices, such as the number of erythrocytes, hemoglobin concentration, hematocrit, and red blood cell distribution width, decreased. There were no statistically significant changes in the number of lymphocytes and thrombocytes, the concentration of totalprotein, albumin, and polyphenols. Conclusions. Prolonged and intense physical exercise, such as a marathon run, causes multiple significant changes in the body. These changes can lead to health disorders and deterioration of physical fitness.